2017
DOI: 10.1016/j.cellsig.2017.02.018
|View full text |Cite|
|
Sign up to set email alerts
|

MKP-1 negatively regulates LPS-mediated IL-1β production through p38 activation and HIF-1α expression

Abstract: Interleukin 1 beta (IL-1β) is a pro-inflammatory cytokine that plays a major role in inflammatory diseases as well as cancer. The inflammatory response after Toll-like receptor (TLR) 4 activation is tightly regulated through phosphorylation of MAP kinases, including p38 and JNK pathways. The activation of MAP kinases is negatively regulated by MAPK phosphatases (MKPs). MKP-1 preferentially dephosphorylates p38 and JNK. IL-1β is regulated through the activation of MAPK, including p38 as well as several transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 46 publications
4
50
0
Order By: Relevance
“…This dataset extends the reproducibility of the recent published data [1]. BMDMs derived from WT and MKP-1 -/- mice exhibit higher p38 and JNK activation in response to LPS (Fig.…”
Section: Datasupporting
confidence: 88%
“…This dataset extends the reproducibility of the recent published data [1]. BMDMs derived from WT and MKP-1 -/- mice exhibit higher p38 and JNK activation in response to LPS (Fig.…”
Section: Datasupporting
confidence: 88%
“…It cannot be ruled out that the artificial situation in cell culture, e.g., the attachment to the cell culture dish or the differentiation with Phorbol-12-myristat-13-acetat, provided enough stimulus for IL-1β secretion. Danger signaling might not be the only mechanisms involved in IL-1β secretion, as it was shown that HIFα, which is stabilized by cobalt ions [24], is involved in IL-1β biosynthesis [35] Interestingly, MCP-1, which was upregulated in debris-induced inflammation [7], was shown to be decreased in gene expression as well as protein biosynthesis after treatment with cobalt and nickel ions in THP-1 macrophages, and was not released from THP-1 monocytes at all despite increased gene expression. A similar effect was observed in THP-1 monocytes for IL-8, which showed a significant elevation in gene expression level, while the protein release was significantly decreased compared to untreated controls.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, DEX pretreatment effectively improved the survival rate of BMDMs and reduces the production of pro‐inflammatory cytokines, such as TNF‐α, IL‐1β, IL‐18 after the addition of HMGB1. The overproduction of these pro‐inflammatory cytokines is thought to require the activation of MAP kinases, including ERK1/2, JNK, and p38 (Zarubin and Han, ; Liu et al, ; Talwar et al, ). Consistently, we also found that DEX reduces the production of pro‐inflammatory cytokines via inhibition of ERK1/2 and P38 phosphorylation in BMDMs in response to HMGB1 treatment.…”
Section: Discussionmentioning
confidence: 99%